2017
DOI: 10.1123/ijspp.2016-0322
|View full text |Cite
|
Sign up to set email alerts
|

Velocity, Oxygen Uptake, and Metabolic Cost of Pull, Kick, and Whole-Body Swimming

Abstract: Implementation of this testing protocol before and after a pull- or kick-training block will enable sport scientists to determine how the velocity contributions and/or metabolic cost of the upper- and lower-limb actions have responded to the training program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 17 publications
(28 reference statements)
0
9
0
2
Order By: Relevance
“…In the first of two 100 m dash trials, the stride frequency showed a larger effect size after PAP [49]. It has been reported that kicking frequency has an effect on metabolic response [50]. The increase in speed due to higher kicking frequency can have the detrimental effect of a larger internal mechanical work.…”
Section: Discussionmentioning
confidence: 89%
“…In the first of two 100 m dash trials, the stride frequency showed a larger effect size after PAP [49]. It has been reported that kicking frequency has an effect on metabolic response [50]. The increase in speed due to higher kicking frequency can have the detrimental effect of a larger internal mechanical work.…”
Section: Discussionmentioning
confidence: 89%
“…Os artigos buscaram diferenças na cinemática e no custo de energia entre os nados e a utilização dos membros inferiores. 14,16,35,39 Também foi apresentada a contribuição das pernas para os quatro nados competitivos, buscando a frequência da ação das pernas na eficiência de propulsão e na coativação muscular durante a ondulação subaquática. 38 Ainda, alguns estudos se atentaram para a relação entre diminuição da velocidade de natação e atividade muscular durante o nado, o que pode ser traduzida como fadiga.…”
Section: Cinemáticaunclassified
“…Bivariate analyses were carried out, establishing relationships between a single determinant domain (notably physiology or biomechanics) and performance. The anaerobic threshold [1][2][3], energy cost [4,5] or time-limit and minimum velocity to achieve the maximal oxygen uptake [6,7] were reported as strongly related to swimming performance. Furthermore, it was determined that those physiological factors seem to depend on biomechanics, such as the stroke kinematics [8], the speed fluctuation [9] and the arm's propelling efficiency [10,11].…”
Section: Introductionmentioning
confidence: 99%